Tolok Ukur Kesepadanan (Kafa’ah) dalam Pernikahan: Perspektif Ibnu ‘Abdil Barr dan Imam Ibnu Al-Humam - Athifatul Wafirah (State Islamic University (UIN) of Sunan Ampel, 2021)
This research is library research that aims to explain the thoughts of scholars regarding the concept of kafa'ah. The method chosen is the descriptive analysis method with a comparative approach, which describes the data regarding the opinion of Ibnu 'Abdil Barr and the opinion of Imam Ibnu Al-Humam about the benchmark of equivalence (kafa'ah) in marriage. The data is then analyzed using comparative analysis. From the results of the study, it was found that Ibnu 'Abdil Barr determined the benchmark of equivalence (kafa'ah) based on the Qur'an, Hadith, and ijma' al-madīnah experts. Meanwhile, Imam Ibnu Al-Humam in determining the criterion of equality (kafa'ah) in marriage is based on the Qur'an, Hadith, and 'urf. Ibnu 'Abdil Barr and Imam Ibnu Al-Humam have the same istinbat method, namely using the Qur'an and Hadith as the main and second basis. The difference between the two lies in determining the benchmark of equivalence (kafa'ah) in terms of religion alone, the basis for strengthening Ibn 'Abdil Barr in determining the benchmark of equivalence on the consensus of al-Madinah experts. Meanwhile, Imam Ibnu Al-Humam determines the benchmark of equivalence (kafa'ah) from five criteria, namely: lineage, independence, religion, wealth and profession. Imam Ibn Al-Humam uses 'urf as a consideration.